Marines an illustrated history : the U.S. Marine Corps from 1775 to the 21st century - Hearn, Chester G. (Zenith Press, 2007)
The Wilde Sau Geschwader JG 300 played a key role in the aerial defense of the Reich during the last two years of WWII but has never before been the subject of a serious and detailed study until now. This work thus fills a major void in the history of the war in the air.